Commentary on: Hairless and the polyamine putrescine form a negative regulatory loop in the epidermis. Issue 11 (29th October 2013) - Ramot, Yuval; Vardy, Leah A.
Abstract: Polyamines are cationic amines essential for cellular proliferation. Recently, their role in hair follicle (HF) growth has started to be explored, but their exact function is still obscure. In the October issue of Experimental Dermatology, Luke et al . follow the observation that putrescine overproducing mice and hairless (HR) mutant mice show a similar clinical phenotype of hair loss and dermal cyst formation. They show that HR and putrescine form a negative regulatory feedback mechanism, which might regulate hair cycling and therefore control hair growth. This study clearly demonstrates that a strong connection exists between HR and polyamines although there are probably additional molecular pathways involved in the polyamine regulation of hair growth which remain to be discovered.